Efeito de diferentes estratégias de fresamento sobre a qualidade de superfícies especulares em aços ferramenta - Castanheira, Lucas Cappucio (Universidade Federal de São Carlos, 2024)
The importance of the plastics industry and the use of this type of material for the most diverse purposes to the development of steel alloys for the manufacturing of injection molds. Mold manufacturing has a direct influence on product delivery time, costs, and quality, and milling is one of the most relevant processes for its production. Given the difficulty in machining hardened steels and the geometries commonly observed in injection molds, besides the necessary surface quality to generate plastic parts without defects, an adequate milling strategy must be chosen, which implies in defining not only the cutting parameters and the tool, but also its trajectory. Thus, the present work focuses on investigating the influence of two different cutting strategies in milling process on the surface quality of convex (constant curvature) surfaces on two types of material. The quality will be evaluated from the different roughness parameters correlated to the quality of the perceived gloss and will be evaluated and be correlated to the characteristics of each material, such as hardness and microstructure. After the tests, in the finishing step it was possible to verify the positive influence of the parallel strategy obtaining the lowest values of average roughness Sa and maximum Sz in both steel alloys VH13IM and VTMPlus in comparison with the zig-zag strategy. Those results were congruent with the generated images from the machined surfaces by the finishing step. The combination of low roughness values with a homogeneous topographic profile of the surface led to a higher brightness and mirror finish.
Effect of different milling strategies on the quality of specular surfaces in tool steels
Keywords: Moldes e matrizes; Brilho; Acabamento; Fresamento; Superfície complexa; Milling; Free-form surface; Molds and dies; Gloss; Finishing; ENGENHARIAS::ENGENHARIA MECANICA::PROCESSOS DE FABRICACAO